Epidemiology of Haemophilus influenzae invasive disease in Portugal, 2011-2016 - Heliodoro, Catarina (2018)
Portuguese Group for the Study of Haemophilus influenzae invasive infection: Centro Hospitalar Baixo Vouga, Aveiro; Centro Hospitalar Barreiro / Montijo; Centro Hospitalar de Coimbra; Centro Hospitalar de Faro; Centro Hospitalar do Porto; Centro Hospitalar do Tâmega e Sousa; Centro Hospitalar Leiria; Centro Hospitalar Lisboa Central; Centro Hospitalar Lisboa Norte; Centro Hospitalar Lisboa Ocidental; Centro Hospitalar Médio Ave / Famalicão; Centro Hospitalar Vila Nova de Gaia / Espinho; Hospital de Braga; Hospital de Santa Luzia, Viana do Castelo; Hospital de Vila Franca de Xira; Hospital Dr. Fernando da Fonseca, Amadora; Hospital Dr. Nélio Mendonça, Funchal; Hospital Garcia da Orta, Almada; Hospital S. João , Porto